Cryopreservation of buffy coat–derived platelet concentrates photochemically treated with amotosalen and UVA light. Issue 11 (3rd October 2018) - Meinke, Stephan; Wikman, Agneta; Gryfelt, Gunilla; Hultenby, Kjell; Uhlin, Michael; Höglund, Petter; Sandgren, Per
Abstract : BACKGROUND: Cryopreserved platelets (CPPs) are considered a promising approach for extended platelet storage, bridging inventory shortages of conventionally stored platelets. It is unknown if platelet concentrates exposed to photochemical treatment (PCT) with amotosalen and ultraviolet A (UVA) light, to inactivate pathogens, are suitable for freezing. The objective of this study was to analyze potential effects of PCT on CPPs as compared with untreated CPPs. STUDY DESIGN AND METHODS: A total of 12 PCT‐treated and 12 untreated platelet units from buffy coats were cryopreserved at −80°C in 5% dimethyl sulfoxide. CPPs of both types were rapidly thawed at 37°C and resuspended in 200 mL fresh plasma. In vitro properties were analyzed prefreezing, postfreezing and thawing, and on Day 1 after thawing. RESULTS: Directly after thawing, no major differences in platelet content, lactase hydrogenase, adenosine triphosphate, mitochondrial membrane potential, CD62P, CD42b, and platelet endothelial cell adhesion molecule were seen between PCT‐CPPs and conventional CPPs. Agonist‐induced PAC‐1 expression and contribution of CPPs to blood coagulation in an experimental rotational thromboelastometry setup were also similar between the groups. On Day 1 after thawing, the CPPs of both types performed less well. The PCT‐CPPs tended to be more affected by the freezing process than the conventional CPPs. CONCLUSIONS: PCT‐CPPs appeared slightly more susceptible to lesion effects by freezing than conventional CPPs, in particular in assays on Day 1 after thawing, but these differences were small relative to the dramatic effects of the freezing process itself.